Profiling Organizational Culture: Using Grid-Group Cultural Theory as a Lens to Take a Snapshot of an Organization’s Culture - Jeroen Maesschalck (SAGE Publishing, 2021)
This article draws from grid-group cultural theory (GGCT) to develop a survey instrument that allows to take an “adequate snapshot” of the culture of an organization. It specifies GGCT’s typology into 15 dimensions, situated in the two-dimensional space defined by the cross-tabulation of the grid and group axes. Those 15 dimensions are operationalized in a questionnaire that is used in two consecutive studies: one in 64 local police forces in Belgium and one in a large ministry of the Belgian federal government. Confirmatory factor analyses largely corroborate the 15-dimensional model. Multidimensional scaling indicates that the 15 dimensions largely take the positions in the two-dimensional space that GGCT would expect them to take. Finally, latent profile analysis identified six cultural profiles (i.e., particular combinations of the dimensions) in the studied work units, showing the potential benefits of a configural approach to the study of organizational culture in public sector organizations.